SURGICAL MANAGEMENT OF CYSTIC ENDOMETRIAL HYPERPLASIA- PYOMETRA COMPLEX WITH UTERINE FIBROADENOMA AND VAGINAL LEIOMYOMA IN A DOG - X, MINU; R S, ABHILASH; JAYAKUMAR, R S; KUMAR , VINAY; P M, SHABEEBA (The Indian Journal of Animal Reproduction, 2021)
A seven-year-old intact German Shepherd bitch was presented to the University Veterinary Hospital, Kokkalaiwith a complaint of bleeding from the vulva and constipation for the past three months. On general examination, theanimal was emaciated, and bleeding was noticed from the vagina. Per vaginal examination revealed the presence ofgrowth in the vaginal cavity. The condition was tentatively diagnosed as cystic endometrial hyperplasia pyometracomplex with a mass in the abdominal cavity and vagina. Exploratory laparotomy was performed under generalanesthesia and ovariohysterectomy (OHE) was carried out, and episiotomy procedure was performed to remove thevaginal mass. Postoperatively animal was managed with antibiotics and supportive therapies, and the animal madean uneventful recovery, further no recurrence was observed. On histopathological examination of the uterine masswas confirmed as fibroadenoma and vaginal mass as leiomyoma. The present case report suggests that dogs sufferingfrom CEH pyometra along with uterine fibroadenoma and vaginal leiomyoma can be successfully managed withsurgical excision of the tumor mass and OHE.
Keywords: CEH-Pyometra; leiomyoma; fibroadenoma